Inheritance, urbanization, and political change in Europe. Issue 1 (31st October 2018) - Popa, Mircea
Abstract: Urbanization and the development of middle and working classes have been proposed as a key explanation for political change in the Western world. This article argues that the traditional inheritance systems practiced across Europe have played an important role in the differential development of these urban classes in the period 1700–1900. Inheritance systems that practice some degree of inequality between heirs will lead to more children, generally younger brothers, leaving the land and taking up urban occupations. A statistical analysis of geographical data shows that regions in which such unequal inheritance was practiced were two to three times more likely to develop urban areas after 1700. This claim is robust to a number of challenges, including country fixed effects, and to only looking at Western Europe. An important mechanism through which the divergence may have occurred is illustrated through a quantitative analysis of pairs of brothers in the UK and Romania, two countries with opposing inheritance traditions.